Pengaruh Pelatihan, Beban Kerja,dan Gaya Kepemimpinan terhadap Produktivitas Karyawan Jendral Kardus Bandung - Dini, Asri Wulan; Rahmi, Palupi Permata; Muttaqin, Ridlwan (Prodi Manajemen, Fakultas Ekonomi, Universitas Pamulang, 2025)
The purpose of this research is to analyze how Jendral Kardus's training, workload, and leadership style impact worker productivity. Thirty one participants made up the sample for this research. The study used SPSS for hypothesis testing, multiple linear regression analysis, correlation coefficient testing, and validity testing. The descriptive analysis yielded modest categories for the following variables: leadership style, workload, training, and staff productivity. Observation and questionnaires were used to gather data. Employee productivity is positively and significantly impacted by training, according to the data. Increases in workload are positively and significantly correlated with gains in productivity. There is a positive and statistically significant relationship between leadership style and staff output. There is a favorable and statistically significant relationship between leadership style, workload, and training all having an impact on staff productivity.